SEBARAN KONSENTRASI LOGAM BERAT DI LAHAN PERTANIAN KABUPATEN WONOSOBO - Triyani Dewi; Cicik Oktasari Handayani; Anik Hidayah; Sukarjo Sukarjo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The agricultural sector is still the leading sector of the economy in Wonosobo Regency. Its superior commodities include paddy rice, tea, tobacco, coffee, and vegetable plants. In the practice of agricultural activities, it is inseparable from the use of inorganic fertilizers and persistent chemical pesticides that cause heavy metal contamination in agricultural land. Industrial waste around agricultural land that enters the water body also contributes to the accumulation of heavy metals in the soil of the water for irrigation. This study aimed to determine the distribution of heavy metal content of Pb, Cd, Ni, Co, Cr, and As on the agricultural land of Wonosobo Regency. The study was conducted on the agricultural land of Wonosobo Regency. As many as 312 soil samples were taken from a layer of sports (depth of 0-20 cm) of agricultural land in ten sub-districts of Wonosobo Regency. Soil sample analysis included heavy metals Pb, Cd, Ni, Co, Cr, As, organic Carbon, CEC, and soil texture. The analysis was carried out in an integrated laboratory, the Agricultural Environment Research Center. The results showed the concentration of heavy metals detected in Wonosobo Regency agricultural land respectively Pb > Co > Ni > Cr > As > Cd. These heavy metals in the soil are still in normal concentrations and are safe for agricultural land.